2010
DOI: 10.1177/1043659609357640
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality and Its Relationships With the Health and Illness of Appalachian People

Abstract: This article explores the ways spirituality intertwines with the health and culture of those living in the Appalachian region. Nursing has long considered the value of spirituality and faith, noting its complex connections with health and illness. Literature pertaining to spirituality, health, and the culture of those residing in the Appalachian region was reviewed. Although the review suggests that connections between spirituality and health exist, empirical evidence is limited, somewhat dated, and lacks viab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 45 publications
2
30
0
Order By: Relevance
“…[64,65] Qualitative description study results have tremendous potential to translate directly to pressing health care situations and provide clear information about ways to improve care. [66] Raine et al [67] found that pregnancy care providers require communications training to encourage empathic interactions that promote constructive provider-user relationships and encourage women to engage effectively and assess the care they need.…”
Section: Discussionmentioning
confidence: 99%
“…[64,65] Qualitative description study results have tremendous potential to translate directly to pressing health care situations and provide clear information about ways to improve care. [66] Raine et al [67] found that pregnancy care providers require communications training to encourage empathic interactions that promote constructive provider-user relationships and encourage women to engage effectively and assess the care they need.…”
Section: Discussionmentioning
confidence: 99%
“…The cultural framework of religion/spirituality is frequently more influential than the cultural framework of medicine (Behringer & Krishnan, 2011). Cancer patients often rely on their church and clergy as a trusted source of information for supplemental or alternative information as an influence on their attitudes and behaviours regarding use of care (Dibble & Denham, 2010). This theme also emerged in community based participatory research studies in the region.…”
mentioning
confidence: 99%
“…To address some of these disparities, researchers must look at what older adults believe is the foundation of their wellness. According to the literature, one important cultural value that appears to support wellness and resilience in Appalachia is spirituality (Diddle & Denham, ; Helton & Keller, ; Linscott, ). By understanding the significance of spirituality, helping professionals can leverage the role of spirituality in wellness among older adults in Appalachia.…”
mentioning
confidence: 99%
“…ARC (n.d.) defined Appalachia as a 205,000‐square‐mile area covering 13 states and 420 counties along the Appalachian Mountains that is home to 25 million people. One in three people are older adults in Appalachia (ARC, n.d.; Diddle & Denham, ; Goins et al, ). As this sector of the population grows, counselors will become increasingly important to service teams trying to meet the needs of older adults (Schwiebert, Myers, & Dice, ).…”
mentioning
confidence: 99%
See 1 more Smart Citation